Exploring factors influencing continuous viewing intention of Chinese documentary programs among undergraduates - Li, Mengyu; Yasin, Megat Al-Imran; Hashim, Norliana; Ang, Lay Hoon; Kang, Hongzhe (Human Resource Management Academic Research Society, 2021)
This article used a qualitative method, using semi-structured interviews to select informants conduct online interviews with undergraduate students in mainland China to explore their continuous viewing intention as audiences towards Chinese documentary programs. Under the guidance of the theory of use and gratification, exploring the factors affecting continuous viewing intention which include cognitive needs, affective needs and tension free needs, and so on. Based on the different needs, they viewed Chinese documentary programs and when their satisfaction is very high, they are more inclined to continue viewing Chinese documentary programs. This study will do quantitative method to verify the UGT model to increase the reliability and validity of research results in the future.